Improving English Middle School Student Learning Achievement By Using Picture Card Media - Hasrida, Hasrida (ETDC: Indonesian Journal of Research and Educational Review, 2024)
Study this aiming For increased results, learn English. Participants educated Class VII with the use of picture card media at SMPN Satap. The results were low, with the pre-test score indicating that the participants were not meeting the mark. The minimum completion is 60. Teachers still use method learning conventional . The solution is to apply picture card learning media to subjects in English lessons. The research conducted is a study action class in two cycles. Each cycle consists of on-stage planning, action, observation, and reflection. Research This was conducted at SMPN Satap Death with subject study participant education in class VII. Data collection techniques are tests, observations, and documentation. The instruments used question tests and observations directly. The data, derived from the test results, was analyzed using percentage variation statistics. Indicators of success study when results Study participant education experience improvement from cycle I to cycle II is in the category of good and very good at least 80% - 89%. By utilizing Picture Card media, you can enhance your results. Study participants educate class VII of SMPN Satap. Cycle I results: We educated study participants to achieve an average value of 54 categories. An adequate increase in 75 categories is a positive outcome. Completion results: Study increased from 45% in cycle I to 100% in cycle II.